Assessing Polychlorinated Biphenyls (PCBs) Contamination in Indoor Dust among University Students in Ilorin, Nigeria - Ezechinyere, Chiemeka Henry; Fiyinfoluwa Alo, Mobisayo (Asian Pacific Journal of Environment and Cancer, 2023)
Background: This study aimed to assess the contamination of Polychlorinated Biphenyls (PCBs) in indoor dust among university students in Ilorin, Nigeria. Methods: One hundred (100) indoor dust samples were collected from different locations within university hostels. Two Universities in Ilorin were sampled for the study; the Univerisity of Ilorin and Al-Hikmah University. Gas chromatography-mass spectroscopy (GC-MS) was employed to analyze and identify fourteen PCB congeners. Results: The results revealed that university students were exposed to low levels of PCB contamination in indoor dust. The concentrations of individual PCB congeners ranged from 4.993ng/g to 37.701ng/g. Notably, PCB-52 and PCB-118 were the predominant congeners, with mean concentrations of 37.701ng/g and 30.928ng/g. Conversely, PCB-44 exhibited the lowest occurrence, with a mean concentration of 4.993ng/g. The study found positive correlations among specific PCB congeners, suggesting familiar sources and environmental behaviors. However, no significant correlations were found between residential characteristics and measured PCB levels. Conclusion: The results emphasize the need for further research to minimize PCB contamination in indoor environments and protect human health. It is recommended that PCB levels be monitored in indoor environments and enforce strong regulations to control PCB production, use, and disposal.